Ubezpieczenie społeczne rolników po wejściu Polski do Unii Europejskiej - Rutkowska, Małgorzata; Kozyra, Przemysław (Farmers Social Insurance after the Integration of Poland into the European Union, 2005)
Poland accession to the European Union and its future membership in the Community affects farmers social insurance. New law gives the right to keep and receive worked out rights e.g. pensions.This means that all benefits will be granted and paid to all the insured on the account of residence. A kind of innovation is transferring pension's rights abroad.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 254-261